2022
DOI: 10.1155/2022/5073059
|View full text |Cite
|
Sign up to set email alerts
|

Composting for a More Sustainable Palm Oil Waste Management: A Systematic Literature Review

Abstract: Palm oil production has increased significantly, specifically in Indonesia and Malaysia. However, this growth has raised environmental concerns due to the high discharge of empty fruit bunches, palm oil mill effluents, and other solid wastes. Therefore, this study aims to examine the treatment of palm oil waste by composting and systematically review insights into its application through a systematic literature review approach. Among the 1155 articles, a total of 135 were selected for a systematic review of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
10
0
3
Order By: Relevance
“…However, elongation at break decreased with most increased fiber content levels. This balance between tensile strength and morphology, underlined by the SEM findings, emphasizes the critical importance of precise fiber treatments [121,122] and loading levels in developing sustainable bioplastics. Another study developed natural fiber-reinforced polymer matrix composites using two different sizes of EFB fibers (605 μm and 633 μm) and acrylic thermoplastic resin.…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 81%
See 2 more Smart Citations
“…However, elongation at break decreased with most increased fiber content levels. This balance between tensile strength and morphology, underlined by the SEM findings, emphasizes the critical importance of precise fiber treatments [121,122] and loading levels in developing sustainable bioplastics. Another study developed natural fiber-reinforced polymer matrix composites using two different sizes of EFB fibers (605 μm and 633 μm) and acrylic thermoplastic resin.…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 81%
“…Furthermore, EFB fibers are composted into nutrient-rich fertilizers, enhancing sustainable agriculture practices [121,122], and used in the production of green materials and biomaterials [123,124]. The morphology of palm oil flower and fruit fibers was studied using scanning electron microscopy, revealing distinct characteristics (Figure 4(a)-(d)).…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Akan tetapi aplikasi TKS segar akan meningkatkan serangan Oryctes ssp. dibandingkan TKS kompos (Supriatna et al, 2018), sehingga penggunaan kompos dibanding aplikasi TKS langsung dapat berkontribusi untuk mengurangi penggunaan pestisida.…”
Section: Dekomposer Limbah Kelapa Sawitunclassified
“…The composting treatment of palm oil waste is studied and systematic literature research is conducted to get a thorough understanding of its possible uses [ 15 ]. The findings demonstrated that composting, which is regarded as a sustainable technology for preserving the environment, human safety, and economic value, provided the best treatment for palm oil waste.…”
Section: Introductionmentioning
confidence: 99%